UPAYA MENINGKATKAN KETERAMPILAN MOTORIK KASAR ANAK MELALUI PERMAINAN TRADISIONAL BENTENGAN - Erna Roostin; Wulanda Aditya Azis; Nida Wahdatul Fuadah (JESA-Jurnal Edukasi Sebelas April, 2022)
The aims of this study is to describe learning activities and the improvement of gross motor skills through children's traditional games of bentengan in Group B students of RA Nurul Falah, Mekarwangi Village, Lemahsugih District, Majalengka Regency. The method used by the researcher in this study was Classroom Action Research (CAR) in Group B students of RA Nurul Falah that consist of 12 people as participants. The design of this research is the model of Kemmis and Mc Taggart. The research data were collected through performance appraisal sheets. Then, the data were analyzed and reflected by using qualitative and quantitative data analysis techniques. The result shows that the traditional game bentengan can improve the gross motor skills of children in group B students in RA Nurul Falah. The average score of all children in the initial conditions reaches 1.3 with a percentage of 0%, the cycle I increases to 2.5 with a percentage of 25%, the cycle II increases to 3.4 with a percentage of 58.3%, then in the cycle III increases to 3.8 with a percentage of 91.6%.